INPATIENT ANTITHROMBOTIC THERAPY FOR MYOCARDIAL INFARCTION : RETROSPECTIVE STUDY - Shofiatul Fajriyah; Dilla Salwa Nur Rohmah; Lelly Winduhani Astuti; Fentyana Dwi Rilawati; Fitria Wahyuning Wulan; Esti Ambar Widyaningrum (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Myocardial infarction (MI), a subtype of coronary heart disease (CHD), is still a major cause of morbidity and mortality around the world. Non-ST-segment elevation MI (NSTEMI) is more common than ST-segment elevation MI (STEMI). Antithrombotic therapy, including antiplatelet and anticoagulant agents, is essential in MI management to prevent thrombus formation and reduce ischemic complications. Although international and national clinical guidelines (PERKI and ACC/AHA) provide recommendations tailored to MI type and patient factors, discrepancies in clinical practice, especially in developing countries, may impact treatment outcomes. This retrospective descriptive study aimed to evaluate the use and appropriateness of antithrombotic therapy in NSTEMI and STEMI patients at Hospital X, Kediri City, in 2018. Data were collected from medical records of hospitalized acute myocardial infarction (AMI) patients. Aspirin combined with clopidogrel was the most commonly used regimen for NSTEMI, whereas STEMI patients frequently received aspirin, clopidogrel, and enoxaparin; fibrinolytics were administered in nine STEMI cases. Dosage evaluation showed compliance with guidelines in NSTEMI patients, while 36.84% of STEMI patients, particularly those receiving enoxaparin, were given incorrect dosages. These findings highlight the need for improved adherence to clinical guidelines to optimize antithrombotic therapy outcomes in MI management